Progressive Regulation of Electrical and Thermal Transport Properties to High‐Performance CuInTe2 Thermoelectric Materials. Issue 12 (5th April 2016) - Luo, Yubo; Yang, Junyou; Jiang, Qinghui; Li, Weixin; Zhang, Dan; Zhou, Zhiwei; Cheng, Yudong; Ren, Yangyang; He, Xu
Abstract : p‐type CuInTe2 thermoelectric (TE) materials are of great interest for applications in the middle temperature range because of their environmentally benign chemical component and stable phase under operating temperatures. In order to enhance their TE performance to compete with the Pb based TE materials, a progressive regulation of electrical and thermal transport properties has been employed in this work. Anion P and Sb substitution is used to tune the electrical transport properties of CuInTe2 for the first time, leading to a sharp enhancement in power factor due to the reduction of electrical resistivity by acceptor doping and the increase of the Seebeck coefficient resulted from the improvement of density of states. Concurrently, In2 O3 nanoinclusions are introduced through an in situ oxidation between CuInTe2 and ZnO additives, rendering a great reduction in the thermal conductivity of CuInTe2 by the extra phonon scattering. Then, by integrating the anion substitution and nanoinclusions, a high power factor of 1445 μW m −1 K −2 and enhanced ZT of 1.61 at 823 K are achieved in the CuInTe2 based TE material. This implies that the synergistic regulation of electrical and thermal transport properties by anion substitution and in situ nanostructure is a very effective approach to improve the TE performance of CuInTe2 compounds. Abstract : A progressive regulation of electrical and thermal transport properties of CuInTe2 is performed through anion (P and Sb) substitution and in situ oxidation of CuInTe2 by ZnO. Using this approach, an unprecedented high power factor of 1445 μW m −1 K −2 and ZT of 1.61 at 823 K has been obtained in the CuInTe1.99 Sb0.01 +1.0 wt% ZnO sample.